MULTIPLE VIEWS: WHAT IT MEANS TO BE BLACK IN BRAZIL - Araujo de Luna, Erica; Santiago de Lima, Erivania; de Fátima Rodrigues de Oliveira, Luisa; de Meneses Silva, Ricardo; Coutinho de Souza, Rubiana (Revista Gênero e Interdisciplinaridade, 2022)
The choice of this theme is justified by the need to better understand the historical and social inequalities that permeate the daily life of the black population and stand out as immense that black peoples still experience in Brazil today. From this perspective, the research aims to identify and elucidate the racial and structural issues that are part of the construction of our society. The article will be briefly presented on the term black, its etymology, racial classification and the study of its genetics; historical analysis of blacks in Brazil and their colonization; the condition of the free black in the context of Brazilian society; History of black people who are nationals and identify themselves at different times. From this contextualization, we will go over structural racism and its contribution to violent deaths against blacks. How do black lives matter? For whom? The methodology used was the bibliography, which contains articles from magazines, books, theses and other perspectives of qualitative research in documents. In view of the research, Brazil is characterized by a conception of racism and that it persists from preconceived and proven attitudes of discrimination. Therefore, ethnic-racial prejudice exists and presents itself through racism and Brazilian cordial behavior, the Brazilian private ones, which are manifested in relationships and are manifested in supposed public tolerance, which can be called racism. It is concluded that the debate on racial prejudice is of great importance for the formation of a conscious and egalitarian society.